Drone technology and its implications to the Malaysian construction industry - Law, Caerin Hui Yen (2021)
The advancement in construction technology is changing the face of the construction industry. Construction technology is reshaping the construction industry by improving the safety, efficiency, productivity, and collaboration in construction projects. Drones, also known as Unmanned Aerial Vehicles (UAV), are one of the recent emerging construction technologies that have been actively adopted by construction industry worldwide. The state of drone adoption in the Malaysian construction industry remains an unknown issue. Does the Malaysian construction industry aware of drone technology? How are drones utilised in the Malaysian construction industry? What are the challenges faced by the Malaysian construction industry? This study aims to explore the application of drone technology in the Malaysian construction industry. Specifically, it investigates the awareness towards drone technology, its applications, and the challenges of drone adoption in the Malaysian construction industry. This study adopted the quantitative research approach where data is collected through questionnaire surveys using Google Form via email and the LinkedIn platform, from 123 contracting companies located within the Klang Valley area. Analysis techniques such as the Cronbach’s alpha reliability test, descriptive analysis, Kruskal-Wallis test, and MannWhitney U test are conducted to interpret the collected data into inferential information. The findings revealed that Malaysian contracting community has a moderate level of awareness towards drone technology. Contractors aged between 25 to 34 years old recorded the highest awareness towards drone technology. Drone adoption level is at 17.89 %, with a total of 22 respondents from Grade 5, 6, and 7 contracting companies to have adopted the drone technology. The three most common applications of drone technology in the Malaysian construction industry are (1) progress monitoring; (2) safety inspection; and (3) security surveillance. The findings also revealed the three most significant challenges of drone adoption in the Malaysian construction industry. The challenges are (1) top management’s support; (2) operational and maintenance costs; and (3) initial costs. As such, this study sought to provide an in-depth insight to increase the construction industry’s awareness towards drone technology and its adoption in Malaysia.